Synthesis and characterization of novel niccolites [(CH3)2NH2][FeIIIMII(HCOO)6] (MII = Zn, Ni, Cu)1. Issue 29 (7th August 2015) - Ciupa, Aneta; Mączka, Mirosław; Gągor, Anna; Pikul, Adam; Ptak, Maciej
<x xml:space="preserve">Abstract</x> We report the synthesis, structural, magnetic, Raman and IR studies of novel niccolite-type heterometallic [(CH3)2NH2][FeIIIMII(HCOO)6] compounds (MII = Ni, Zn and Cu). The Ni and Cu compounds order ferromagnetically at 42 and 28.5 K, respectively. The monoclinic Cu member exhibits different structural changes on cooling than the trigonal Zn and Ni compounds.